Effect of red rice on the lipid profile and risk of cardiovascular diseases - Lazar, Michał; Miszczyk, Karolina; Maj, Patrycja; Sergiel, Natalia; Kania, Agata; Gonet, Malwina; Włodarczyk-Cybulska, Karolina; Mozer, Piotr; Maternia, Jakub; Serwik-Trandasir, Aleksandra (Journal of Education, Health and Sport, 2023)
Red yeast rice (RRY) and its ingredient, monacolin K, are increasingly being studied for their potential effects on the lipid profile and risk of cardiovascular diseases. This article presents an overview of the latest research on this topic, including randomized controlled trials and systematic reviews, Analysis of medical standards, that RRY supplementation can lower LDL cholesterol and triglycerides, which can prevent development of cardiovascular diseases. Studies have also seen beneficial changes in other parameters, including levels of total cholesterol, endothelial funciton and arterial stiffness. Substantially, additional and larger studies are needed to confirm long-term safety of RRY. All of this indicates, that RRY can be a tool in the fight against dyslipidemia and cardiovascular diseases, especially in people who cannot tolarate statins.